2017
DOI: 10.4236/acs.2017.74030
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis in Standardized Precipitation Index and Standardized Anomaly Index in the Context of Climate Change in Southern Togo

Abstract: Rainfall and temperature are climatic variables mostly affected by global warming. This study aimed to investigate the temporal trend analysis in annual temperature and rainfall in the Southern Togo for the 1970-2014 period. Daily and annual rainfall and temperature were collected from four weather stations at Atakpame, Kouma-Konda, Lome, and Tabligbo. The temperature variability was determined by the Standardized Anomaly Index (SAI) and the annual rainfall variability was determined using the Standardized Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 25 publications
4
36
0
4
Order By: Relevance
“…It is commonly used to categorize observed rainfall as a standardized departure with respect to a rainfall probability distribution function and to determine the rarity of a drought on a given time scale. The index has been widely used by many researchers [39][40][41][42]. It also has been adopted by the US National Drought Mitigation Center for operational use to replace the traditional Palmer Drought Severity Index.…”
Section: Methods and Datamentioning
confidence: 99%
“…It is commonly used to categorize observed rainfall as a standardized departure with respect to a rainfall probability distribution function and to determine the rarity of a drought on a given time scale. The index has been widely used by many researchers [39][40][41][42]. It also has been adopted by the US National Drought Mitigation Center for operational use to replace the traditional Palmer Drought Severity Index.…”
Section: Methods and Datamentioning
confidence: 99%
“…Pan evaporation varied with [20]. Koudahe et al [21] also found increasing Standardized Anomaly Index in the same location due to an increasing trend in air temperature.…”
Section: Trend In Annual Pan Evaporationmentioning
confidence: 99%
“…The SPI was developed primarily for def ining and monitoring drought. Following Komlan et al (2017), the SPI is calculated through the following steps:…”
Section: Standardized Precipitation Index Estimation Modelmentioning
confidence: 99%
“…Several time scales are used for the computation of SPI on which changes in precipitation can affect different aspects of the water cycle (Komlan et al, 2017). In this study, we evaluated the SPI at timescales of 6 and 12 months.…”
Section: Standardized Precipitation Index Estimation Modelmentioning
confidence: 99%